DETERMINANTS OF INVESTORS DECISION MAKING: A CASE STUDY IN THE INDONESIA STOCK EXCHANGE (IDX) - Thohiri, Roza; Yuni, Revita; Hastuti, Pebri (Universitas Negeri Medan, 2020)
Inflation in Indonesia tends to perform an issue for investors with regards to the yield value from the investment instrument they put in. The capital market in Indonesia is currently promoting stake in shares with the slogan